Extremely large size VSD with pulmonary stenosis - Kumar, J. Rajendra; Kumar, T. Sanath (International Journal of Research in Medical Sciences, 2017)
Defect in the ventricular septum with obstruction to right ventricular outflow tract encompass a wide anatomic, physiological & clinical spectrum. Large ventricular septal defects occur with pulmonary stenosis that varies from mild to severe to complete (pulmonary atresia). Very large VSD (size 6.4cm, in our case) with severe PS is a rare CHD & without surgical correction only 10% patients can survive beyond 20 year of age. With the help of noninvasive investigation (echocardiography) we can diagnose CHD very easily.